2017
DOI: 10.1093/jscr/rjx035
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of double pyramidal lobe on total thyroidectomy: a rare case report

Abstract: Double pyramidal lobe is a scarce anatomical variation of the thyroid gland. Its presence impinges on the completeness of total and subtotal thyroidectomy and the postoperative treatment. Surgeons should be always aware of this variation in order to perform sufficient resection of the thyroid gland and minimize the possibility of recurrence of benign and malignant thyroidopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In the previous research conducted with different sample groups, with the diversities of the cadavers' nationalities and the places and the times of study, showed that the percentages of thyroid gland abnormality (18-66 %) were higher than the one found in this research [11][12][13][14][15][16]. In 2017, pyramidal lobe emergence case was reported [17] ( [26].…”
Section: Discussionmentioning
confidence: 61%
“…In the previous research conducted with different sample groups, with the diversities of the cadavers' nationalities and the places and the times of study, showed that the percentages of thyroid gland abnormality (18-66 %) were higher than the one found in this research [11][12][13][14][15][16]. In 2017, pyramidal lobe emergence case was reported [17] ( [26].…”
Section: Discussionmentioning
confidence: 61%
“…In fact, surgeons generally find a single pyramidal lobe. Conversely, the presence of double pyramidal lobes is extremely rare, and we could find only three previous cases in the English literature ( 3 , 4 , 5 ). All the reported patients with double pyramidal lobes were women who had various thyroid diseases indicating surgical intervention ( Table 1 ).…”
mentioning
confidence: 67%
“…In another study, however, this abnormality was found at 21.6 % (Ranade et al). These thyroidal gland abnormality are susceptible to the operation of radiology physicians and surgeons in thyroidectomy and tracheostomy performances (Gurleyik et al;Sinos & Sakorafas, 2015;Kaklamanos et al, 2017). Being well acknowledge about the thyroidal anatomical change crucial step prior to giving treatment to the patients with thyroid gland abnormality (Rajkonwar & Kusre).…”
Section: Discussionmentioning
confidence: 99%